Representation of Fictional Characters with Disabilities in Selected Crime Novels of Oͅládèͅjoͅ Òkédìjí - Oͅlálérè Adéyeͅmí (Yoruba Studies Review, 2023)
Scholars of Yorùbá literary criticism have not done much in the area of disability studies; therefore, there is a paucity of critical works on the representation of people with disability in Yorùbá novels. This study intended to fill the gap.  The objectives of the study, therefore, were to examine the representation of fictional characters with disabilities in Oͅládèͅjoͅ Òkédìjí’s crime novels particularly Bínú ti rí and Àgbàlagbà Akàn; assess the message of the novelist, and the implications of those representations for the society within the social and charity models of disability theory. The findings of the study showed that Òkédìjí represents the blind and cognitively impaired persons in a positive manner through his modes of projected characterization. He identifies with the plights of a person with a disability, they are mostly victims of poverty, hunger, and crimes in the Post-colonial Nigerian society; and treats all the fictional characters with dignity and honor in line with Yorùbá thoughts and beliefs.  Òkédìjí rejects through his characterization technique and use of proverbs, the insidious kind of social categorization and stigmatization that carry with it a ‘devalued status’ for disabled people prevalent in the modern time as against the Yorùbá culture which regards those living with disability as ‘Eͅni-Òrìsà’ (offspring of the deity). The paper concluded that the message of the novelist about people with disabilities is that disability is not an element of inability; there is ability in disability if society projects a positive image of people with disabilities.